Adapting the electrical power trading company for the operation of Vietnam competitive generation market - Pham, Xuan Thanh; Swierzcek, Fredric William; Sununta Siengthai; Do, Ba Khang; Vietnam Electricity and Norwegian Electricity Corporation (Pathumthani : Asian Institute of Technology, 2012)
In order to operate the Vietnamese Competitive Generation Market, Vietnam Electricity together with Electricity Regulatory Authority of Vietnam proposed suggestion to form Electrical Power Trading Company (EPTC) as a subsidiary of Vietnam Electricity. EPTC was formed in 2007 and has been operated for five years. Vietnamese Competitive Generation Market is officially operated in July 2012 and the reality of the market shows that many problems were not been taken into account when the model of the market was built. EPTC{u2019}s current organization naturally exposed inadequate aspects and restructuring EPTC become an urgent action to ensure the effective operation of the Company in the new period. Through researching the functions, obligations and organization of EPTC and its difficulties when Vietnamese Competitive Generation Market operates, the report aim to propose some solutions to enhance the effect of EPTC{u2019}s operation.
A project report submitted in partial fulfillment of the requirements for the Degree of Master of Business Administrator (Executive) in Energy Management, School of Management
Keywords: Electric utilities -- Marketing -- Vietnam